USE OF GEOTECHNOLOGIES IN SUPPORT OF LAND REGULARIZATION PROCESS IN THE MUNICIPALITY OF SÃO JOSÉ DO GOIABAL (MG) - Krause, Marcelo Batista; Soares, Wesley Oliveira; Silva, Marco Antonio Saraiva da [UNESP]; Faria, Andre Luiz Lopes de; Sant'Amaro, Vitor Thomas; Sousa, Luiz Fellipe Chaves de (Univ Federal Fluminense, 2024)
Urbanization modifies and transforms the urban space. Spatial occupation must be accompanied and regulated as the lack can lead to territorial inequality. Due to social disparities in cities, Urban Land Regularization (Reurb), as an example of public policy, aims at territorial regulation to ensure access to basic rights outlined in the Federal Constitution. Municipal territorial management and planning are essential to ensure the development and growth of a city. In light of this, to facilitate and expedite the decision-making process, the use of geotechnologies such as Remotely Piloted Aircraft (RPAs) and geodetic positioning devices like those employing the Real-Time Kinematic (RTK) system has become common. RPAs and RTK enable the rapid production of data and information with high precision and quality, making them essential tools for aiding in the management and spatial planning process. Through the combination of geotechnologies, with the aim of supporting the territorial management process through Reurb, 174 plans were produced, including 155 for plots, 18 for blocks, 1 for the neighborhood, and 18 tabular memorials describing each plot, categorized by blocks. This model adhered to the requirements set by the property registry office. Using RPA, a georeferenced, corrected high-resolution spatial image was produced and utilized in fieldwork to represent the neighborhood. In conjunction with geotechnologies and for public policies, especially at the municipal level, it is necessary to establish a prior Territorial Registry (TR) to clearly identify the demands of the population and the municipality, ensuring efficiency in the investment of public resources. The combination of TR, RPA, and RTK allowed for the generation of a georeferenced database of the neighborhood at a scale suitable for urban planning. All the produced data provides the local government with excellent tools that will aid in decision-making during the urban management and planning process, with a focus on territorial organization.
Keywords: Land Management; RTK; RPA; GIS